Integrated environmental risk assessment of rare earth elements mixture on aquatic ecosystems - Lachaux, Nicolas; Cossu-Leguille, Carole; Poirier, Laurence; Gross, Elisabeth Maria; Giamberini, Laure (Frontiers in Environmental Science, 2022)
Rare Earth elements (REE) have become essential in strategical sectors such as high- and green-technologies. Their increasing use in human activities worldwide leads to anthropogenic REE releases detectable in all compartments of the environment, transforming REE into emerging contaminants. However, their potential impacts on ecosystems are still poorly understood. In order to have a comprehensive understanding of REE ecotoxicology and to properly assess their environmental risk, we analysed the toxicity of three representative REE (neodymium Nd, gadolinium Gd, and ytterbium Yb). Following recommendations of the European Chemicals Agency, we assessed REE hazard by performing standard ecotoxicological tests on three freshwater species belonging to different trophic levels (algae, crustacean and fish). EC50 were calculated using different modes of expression of REE exposure concentration (based on nominal, measured total and dissolved concentrations) in order to more properly and accurately determine REE toxicity. In order to get closer to environmental conditions, we also tested the toxicity of REE in mixture because all of them occur naturally as such in the environment. Moreover, we added dissolved organic matter (DOM) in the test medium because DOM is ubiquitous and drives REE speciation in freshwater systems. The Results showed that DOM significantly reduced REE bioaccumulation and toxicity, probably by formation of non-bioavailable REE-DOM complexes. The algal species was the most sensitive to REE. Despite slight differences between Nd, Gd and Yb in behaviour and bioaccumulation, the three REE exhibited comparable toxicity and additive effects in mixture to all tested organisms. Thus, we considered REE as a uniform group and, for the first time, we used mixture toxicity values and environmental mixture concentrations to assess the risk of REE in freshwater (instead of considering different REE separately). The results revealed that the risk is currently limited to wastewater treatment plants, and industrial and mining activities, where released quantities of REE can induce severe damage to exposed freshwater organisms. However, the risks are likely more widespread in the future because anthropogenic REE releases are expected to increase.